2017
DOI: 10.1128/jcm.00298-17
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Whole-Genome Sequencing and Reporting of Drug Resistance Profiles on Clinical Cases of Mycobacterium tuberculosis in New York State

Abstract: Whole-genome sequencing (WGS) is a newer alternative for tuberculosis (TB) diagnostics and is capable of providing rapid drug resistance profiles while performing species identification and capturing the data necessary for genotyping. Our laboratory developed and validated a comprehensive and sensitive WGS assay to characterize Mycobacterium tuberculosis and other M. tuberculosis complex (MTBC) strains, composed of a novel DNA extraction, optimized library preparation, pairedend WGS, and an in-house-developed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
90
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(113 citation statements)
references
References 56 publications
9
90
1
1
Order By: Relevance
“…WGS performances have been shown to be accurate and reliable compared to conventional phenotypic diagnostics (species identification: 93%, 95% CI: 90–96%; drug susceptibility accuracy: 93%, 95% CI: 91–95%), with turn‐around time and costs competitive with conventional diagnostics (median of 9 days, interquartile range (IQR): 6–10 for WGS vs a median of 31 days, IQR: 21–44 for conventional diagnostics, with a saving of 7% annually) . The introduction of WGS in routine diagnostics was found accurate (species identification accuracy: 99%; drug susceptibility accuracy: 96% for eight drugs) and rapid (72 h for WGS vs 28 days for DST only), allowing to replace seven different molecular assays and accelerating reporting time . WGS was also successfully used for drug resistance surveillance purposes …”
Section: Molecular Dstmentioning
confidence: 99%
See 1 more Smart Citation
“…WGS performances have been shown to be accurate and reliable compared to conventional phenotypic diagnostics (species identification: 93%, 95% CI: 90–96%; drug susceptibility accuracy: 93%, 95% CI: 91–95%), with turn‐around time and costs competitive with conventional diagnostics (median of 9 days, interquartile range (IQR): 6–10 for WGS vs a median of 31 days, IQR: 21–44 for conventional diagnostics, with a saving of 7% annually) . The introduction of WGS in routine diagnostics was found accurate (species identification accuracy: 99%; drug susceptibility accuracy: 96% for eight drugs) and rapid (72 h for WGS vs 28 days for DST only), allowing to replace seven different molecular assays and accelerating reporting time . WGS was also successfully used for drug resistance surveillance purposes …”
Section: Molecular Dstmentioning
confidence: 99%
“…160 The introduction of WGS in routine diagnostics was found accurate (species identification accuracy: 99%; drug susceptibility accuracy: 96% for eight drugs) and rapid (72 h for WGS vs 28 days for DST only), allowing to replace seven different molecular assays and accelerating reporting time. 161,162 WGS was also successfully used for drug resistance surveillance purposes. 163,164 The advances in performances of NGS workflow (from DNA extraction to data analysis) allowed to improve WGS for 'real-time' routine diagnosis in direct clinical samples, with MTB complex detection accuracy of >97%.…”
Section: Sequencingmentioning
confidence: 99%
“…A prospective British study on mycobacterial diagnosis concluded that WGS accurately identified species and antibiotic resistance with 93% accuracy; moreover, WGS diagnosed a case of multidrug‐resistant tuberculosis before the routine diagnosis was accomplished (Pankhurst et al, ). A similar WGS tuberculosis study from the United States reported 99% accuracy, and a concordance of 96% between WGS and culture‐based diagnostics (Shea et al, ). Moreover, the latter study concluded that applying WGS of tuberculosis cases allowed the reporting of resistance profiles to physicians on average 9 days sooner than with culture‐based diagnostics for first‐line antibiotics, and 32 days sooner for second‐line antibiotics.…”
Section: Whole Genome Sequencing For Identifying Antibiotic Resistancmentioning
confidence: 90%
“…WGS of clinical isolates allows for accurate identification of established-resistance-conferring chromosomal mutations [10, 12, 13] and may ensure adequate treatment in days instead of months. We compared whole genome-based drug resistance profiles with two culture-based quantitative DST methods for a total of 11 drugs, including all first-line drugs (rifampicin, isoniazid, ethambutol, pyrazinamide, streptomycin) and an array of second-line drugs (rifabutin, amikacin, kanamycin A, capreomycin, moxifloxacin, ethionamide).…”
Section: Introductionmentioning
confidence: 99%